Empowering Future Educators: Analyzing Digital Literacy Skills in Elementary Teaching Assistants (TAs) - Rizky Amelia; Ahmad Suriansyah; Aslamiah Aslamiah; Maimunah Maimunah; Celia Cinantya; Wahdah Revia Rafianti (The Innovation of Social Studies Journal, 2025)
Digital literacy skills are essential for leveraging technological advancements and addressing various challenges in the era of Society 5.0. This study aims to analyze the digital literacy competencies of elementary teaching assistants and their preparedness to support digital learning environments. A quantitative descriptive research method was employed, with a population consisting of 246 fifth-semester students from the Elementary Teacher Education Program at the Faculty of Teacher Training and Education, Universitas Lambung Mangkurat, during the 2024/2025 academic year. A sample of 70 students was selected using a simple random sampling technique. Data collection was conducted through a structured questionnaire assessing digital literacy skills. The data analysis employed descriptive statistical methods to evaluate digital literacy levels across multiple competencies. The findings indicate that 49.2% of respondents demonstrated proficiency in functional skills, creativity, collaboration, communication, information retrieval and selection, critical thinking and evaluation, cultural and social understanding, and e-safety. However, 65.2% of respondents struggled with effectively searching for and selecting information across six digital literacy dimensions. Based on the initial data analysis, it is concluded that the digital literacy skills of students in the Elementary Teacher Education Program are categorized as "insufficient." Further interventions are necessary to ensure that future educators develop the competencies required to adapt to technological advancements and become proficient in digital learning environments.